2001
DOI: 10.1211/0022357011777936
|View full text |Cite
|
Sign up to set email alerts
|

Riluzole suppresses post-sigh, but not spontaneous apnoeas during sleep in rats

Abstract: We conducted this experiment to determine the role of glutamate in the mechanism of sleep apnoeas by administering riluzole, a glutamate release inhibitor, to freely moving rats in which sleep-related apnoeas are physiological phenomena. Adult Sprague-Dawley rats were implanted with electrodes for electroencephalogram (EEG) and electromyogram (EMG) recording to monitor sleep and were placed inside a single-chamber plethysmograph to monitor respiration. Sleep and respiration were recorded for 6 h following intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Based on previous dose-ranging experiments done in our laboratory, phenytoin (administered at 20 mg/kg ip) results in a circulating concentration of ϳ100 M, which is the in vitro dose used. The in vivo dosages are within the therapeutic ranges for humans (33,43,68) and were previously used for animal studies (49,55). Control groups received similar volumes of the drug vehicle, DMSO (8 ml/kg).…”
Section: Methodsmentioning
confidence: 99%
“…Based on previous dose-ranging experiments done in our laboratory, phenytoin (administered at 20 mg/kg ip) results in a circulating concentration of ϳ100 M, which is the in vitro dose used. The in vivo dosages are within the therapeutic ranges for humans (33,43,68) and were previously used for animal studies (49,55). Control groups received similar volumes of the drug vehicle, DMSO (8 ml/kg).…”
Section: Methodsmentioning
confidence: 99%
“…The post-sigh apnea is an important manifestation of a central apnea (Eckert et al, 2007a; Radulovacki et al, 2001; Saponjic et al, 2007). Post-sigh apneas are very common in children (Haupt et al, 2012; O'Driscoll et al, 2009) but are also present in adults (Vlemincx et al, 2010).…”
Section: The Recovery From Airway Occlusionmentioning
confidence: 99%
“…Further, since an inhibitor of central glutamatergic neurotransmission, riluzole, decreased the number of PSA, but did not that of SA in the rat (Radulovacki et al, 2001), different mechanisms are suggested to be involved in the generation of each type of apnea. Consistently, the present results also demonstrated differences between SA and PSA in characteristics of apneic events and in responsiveness to progesterone.…”
Section: Discussionmentioning
confidence: 91%